Inborn Errors of Immunity in Adults with Autoimmune Liver Diseases - Ayar, Şefika Nur; Soyak Aytekin, Elif; Şimşek, Cem; Dağ, Osman; Çağdaş, Deniz; Balaban, Yasemin H. (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Inborn errors of immunity (IEI) may associate with autoimmune diseases, including autoimmune liver diseases (AILD). However, both the IEI frequency and secondary effects of immunosuppressives are unknown in patients with AILD due to the lack of data. We aimed to evaluate the ratio of IEI in AILD. Materials and Methods: A total of 82 patients with AILD (39 autoimmune hepatitis, 32 primary biliary cholangitis, 7 variant syndromes (VS), and 4 primary sclerosing cholangitis patients) were included in this single-center, cross-sectional, and descriptive study. The patients were evaluated and classified according to diagnostic criteria for IEI. Results: Out of 82 patients with AILD, female/male ratio was 3.6. Median age of diagnosis of AILD was 45 years. We diagnosed 15 (18%) patients with immunodeficiency (ID). Inborn errors of immunity ratio was highest in VS patient group (29%). Out of 15 patients with ID, 4 (4.8%) patients had common variable immunodeficiency, 4 (4.8%) had partial immunoglobulin A deficiency, 4 (4.8%) had selective immunoglobulin M deficiency, and 3 (3.6%) had combined immunodeficiency. Conclusion: We detect ID in about one-fifth of the patients with AILD. The present study showed a significant risk of IEI that is blurred by the shadow of immune suppressive treatments. We suggest that the AILD patients with ID will benefit from the individualized and targeted therapeutic options used in IEI. Further research with larger patient groups and long-term follow-up are desperately needed to elucidate the diagnostic, therapeutic, and prognostic impacts of IEI-related individualized therapy on AILD patients. Cite this article as: Ayar ŞN, Soyak Aytekin E, Şimşek C, Dağ O, Çağdaş D, Balaban YH. Inborn errors of immunity in adults with autoimmune liver diseases. Turk J Gastroenterol. 2024;35(7):560-567.